Potensi Pola Perjalanan Wisata Berdasarkan Interpretasi Wisata Warisan (Studi Kasus Situs Pugung Raharjo Lampung Timur) - Silalahi, Agnes Tresia (Sabda: Jurnal Kajian Kebudayaan, 2024)
Great nations must be involved in preserving heritage sites to establish a real connection between a nation's past, present, and future. One of them is the Pugung Raharjo Site, which depicts the history and culture of the past Lampung people. Increasing awareness of the Site allows everyone worldwide to share ownership and responsibility for the Pugung Raharajo Archaeological Site. One effort is to identify potential tourist travel patterns so that the site will become a symbol of modernity and function as a wall to prevent the deconstruction of modernity. The qualitative method used in this research is a basis for interpreting history and culture data collection techniques, namely observation, interviews, and literature study. Potential travel patterns formed. Three travel patterns are formed based on motivation, distance, and time between destinations. The first travel pattern is the travel pattern of tourists who want to know the experiences and knowledge of the history and culture of Lampung society at the Pugung Raharjo site and its related destinations. The next pattern is the travel pattern of tourists who want to know the experience and knowledge of the formation of history and culture at the Pugung Raharjo Site from the Hindu-Buddhist Kingdom era and the Islamic Kingdom era. Interpretation and connection between history and culture are the main things in creating travel patterns. The travel patterns that are formed in the future can be used as a marketing strategy for destinations and tour packages so that destination development can have a wider impact.